1996
DOI: 10.1021/es950862d
|View full text |Cite
|
Sign up to set email alerts
|

Sampling and Analysis Artifacts Caused by Elevated Indoor Air Polychlorinated Biphenyl Concentrations

Abstract: Polychlorinated biphenyl (PCB) concentrations were measured in the indoor air of several public buildings in Bloomington, IN. The concentrations ranged from 5 to 300 times higher than outdoor concentrations, and the indoor air PCB levels were highest in buildings with the earliest construction dates; see Figure . These elevated indoor air PCB levels have caused contamination in sample preparation as well as artifacts in sample collection. PCBs in procedural blanks in a laboratory with an indoor air PCB concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…PCAs (C 10 -C 13 , 60-70% Cl) were also detected in DCM (0.15 mg l -1 ) left to evaporate in an open flask overnight; it was unclear, however, whether contamination was a result of airborne PCAs or was from the DCM itself [28]. Similar problems have been encountered with airborne PCB contamination of analytical labs [65]. Significant procedural blanks result in higher method detection limits, i.e., the mean plus three times the standard deviation in the background signals from procedural blanks (sodium sulfate) [14,66,67].…”
Section: Quality Assurancementioning
confidence: 99%
“…PCAs (C 10 -C 13 , 60-70% Cl) were also detected in DCM (0.15 mg l -1 ) left to evaporate in an open flask overnight; it was unclear, however, whether contamination was a result of airborne PCAs or was from the DCM itself [28]. Similar problems have been encountered with airborne PCB contamination of analytical labs [65]. Significant procedural blanks result in higher method detection limits, i.e., the mean plus three times the standard deviation in the background signals from procedural blanks (sodium sulfate) [14,66,67].…”
Section: Quality Assurancementioning
confidence: 99%
“…Other possible sources for indoor PCBs are believed to be data screen terminals (Digernes and Astrup, 1982), ceiling tiles (Anonymus, 1988) and fluorescent lights (Harris, 1985). It was reported that the concentration of PCBs in indoor air can be at least an order of magnitude higher than outdoor air (Balfanz et al, 1993;Vorhees et al, 1997;Wallace et al, 1996), although the sources are not completely clear. A recent publication from Great Britain found a daily average total PCB intake of 0.49 μg/person/day for adults of which 30.6% (4.2 -63%) was derived from inhalation exposure (Harrad et al, 2006).…”
mentioning
confidence: 99%
“…The concentration of PCBs can be at least an order of magnitude higher indoors than outdoors (Wallace et al, 1996;Vorhees et al, 1997), although not all PCB sources are known. Ambient PCB concentrations were reported to have declined slowly from the 1980s to the 1990 by one study (Vorhees, 2001), but another study has suggested no significant decline in PCBs between 1997 and 2005 .…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%